Impact of the Desert dust on the summer monsoon system over Southwestern North America - C. Zhao; X. Liu; L. R. Leung (Atmospheric Chemistry and Physics, 2012)
The radiative forcing of dust emitted from the Southwest United States (US) deserts and its impact on monsoon circulation and precipitation over the North America monsoon (NAM) region are simulated using a coupled meteorology and aerosol/chemistry model (WRF-Chem) for 15 years (1995–2009). During the monsoon season, dust has a cooling effect (−0.90 W m−2) at the surface, a warming effect (0.40 W m−2) in the atmosphere, and a negative top-of-the-atmosphere (TOA) forcing (−0.50 W m−2) over the deserts on 24-h average. Most of the dust emitted from the deserts concentrates below 800 hPa and accumulates over the western slope of the Rocky Mountains and Mexican Plateau. The absorption of shortwave radiation by dust heats the lower atmosphere by up to 0.5 K day−1 over the western slope of the Mountains. Model sensitivity simulations with and without dust for 15 summers (June-July-August) show that dust heating of the lower atmosphere over the deserts strengthens the low-level southerly moisture fluxes on both sides of the Sierra Madre Occidental. It also results in an eastward migration of NAM-driven moisture convergence over the western slope of the Mountains. These monsoonal circulation changes lead to a statistically significant increase of precipitation by up to ~40 % over the eastern slope of the Mountains (Arizona-New~Mexico-Texas regions). This study highlights the interaction between dust and the NAM system and motivates further investigation of possible dust feedback on monsoon precipitation under climate change and the mega-drought conditions projected for the future.